2016
DOI: 10.3892/or.2016.4619
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis in hepatocellular carcinoma

Abstract: Epigenetic changes as well as genetic changes are mechanisms of tumorigenesis. We aimed to identify novel genes that are silenced by DNA hypermethylation in hepatocellular carcinoma (HCC). We screened for genes with promoter DNA hypermethylation using a genome-wide methylation microarray analysis in primary HCC (the discovery set). The microarray analysis revealed that there were 2,670 CpG sites that significantly differed in regards to the methylation level between the tumor and non-tumor liver tissues; 875 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…These evidences suggested that the broad scope of DNA hypomethylation influenced HCC profoundly and potential biomarkers might be detected from hypomethylated genes. Some hyperm-ethylated promoter genes identified in the current study have been reported in recently published studies, such as TBX15, RASSF10, AKR1B1, CDKL2, and ZNF154 10,13. Consistent with a previous study, S100A8 was presented a lower methylation level in HCC tissues compared to adjacent tissues 22.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These evidences suggested that the broad scope of DNA hypomethylation influenced HCC profoundly and potential biomarkers might be detected from hypomethylated genes. Some hyperm-ethylated promoter genes identified in the current study have been reported in recently published studies, such as TBX15, RASSF10, AKR1B1, CDKL2, and ZNF154 10,13. Consistent with a previous study, S100A8 was presented a lower methylation level in HCC tissues compared to adjacent tissues 22.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the tumor-specific DNA methylations have been proposed to be potential diagnostic or prognostic biomarkers 10,11. Aberrant DNA methylations have been frequently found in HCC, which contributed to carcinogenesis by transcriptional silencing of tumor-suppressor genes (TSGs) 12,13. Recent studies have attempted to find promising epigenetic aberrations to evaluate prognosis 14,15.…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic etiology of HCC has been characterized at a genome-wide scale in human tissue and animal models, 17,18,26 whereas much less is known about the role of the epigenome in fatty liver disease and how it may predispose to cancer. In diet-induced fatty liver, potentially compromised function of liverspecific enhancers attributed to elevated 5 mC, in combination with the ubiquitous loss of methylation at other developmentally repressed tissue-specific enhancers, may lead to cell de-differentiation, trans-differentiation, and loss of tissue identity events known to contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation of these CpG islands was overall lower in the tumor tissues than in the matched adjacent tissues (Fig. D), with a higher variability between patients in the tumor samples than in the adjacent tissues, suggesting a deregulation of the methylation status in the tumors, as already reported for HCC . To complement these results, miR‐146b‐5p expression levels of 40 HCC tumor tissues, for which both information on the miR‐146b‐5p expression levels and the methylation status was available, were compared to the corresponding adjacent “normal” tissues (Fig.…”
Section: Resultsmentioning
confidence: 57%